Cold War monks : Buddhism and America's secret strategy in Southeast Asia - Ford, Eugene Brassel (New Haven : Yale University Press, 2017)
"How did the U.S. government make use of a "Buddhist policy" in Southeast Asia during the Cold War despite the American principle that the state should not meddle with religion? To answer this question, Eugene Ford delved deep into an unprecedented range of U.S. and Thai sources and conducted numerous oral history interviews with key informants. Ford uncovers a riveting story filled with U.S. national security officials, diplomats, and scholars seeking to understand and build relationships within the Buddhist monasteries of Southeast Asia. This fascinating narrative provides a new look at how the Buddhist leaderships of Thailand and its neighbors became enmeshed in Cold War politics and in the U.S. government's clandestine efforts to use a predominant religion of Southeast Asia as an instrument of national stability to counter communist revolution"--
The Buddhist world and the United States at the onset of the Cold War, 1941--1954 -- Washington formulates a Buddhist policy, 1954--1957 -- Thailand and the international Buddhist arena, 1956--1962 -- Reforming the monks : the Cold War and clerical education in Thailand and Laos, 1954--1961 -- Thailand and the international response to the 1963 Buddhist crisis in South Vietnam -- Enforcing the code : South Vietnam's "struggle movement" and the limits of Thai Buddhist conservatism -- Thailand's Buddhist hierarchy confronts its challengers, 1967--1975 -- The rage of Thai Buddhism, 1975--1980 -- Conclusion : from Byoto to Kittivudho.
Includes bibliographical references (pages 347-361) and index.
Print version record
In English.
eBooks on EBSCOhost
Keywords: Buddhism and politics -- Thailand; Buddhism and politics -- Southeast Asia; Buddhism -- Thailand -- History; Buddhism -- Southeast Asia -- History; Bouddhisme et politique -- Thaïlande.; Bouddhisme et politique -- Asie du Sud-Est.; Bouddhisme -- Thaïlande -- Histoire; Bouddhisme -- Asie du Sud-Est -- Histoire; RELIGION -- Comparative Religion; HISTORY -- United States -- 20th Century; Buddhism; Buddhism and politics; Southeast Asia; Thailand; History